Songs of nature John Sallis ; on paintings by Cao Jun - Sallis, John C. 1938- (Indiana University Press, 2020)
"This latest philosophical text by John Sallis is inspired by the work of contemporary Chinese painter Cao Jun. It carries out a series of philosophical reflections on nature, art, and music by taking up Cao Jun's art and thought, with a focus on questions of the elemental. Sallis's reflections are not a matter of simply relating art works to philosophical thought, as theoretical insights and developments run throughout Cao Jun's writings and inform many of his artistic works. Sallis maintains abundant points of contact with Chinese philosophical traditions but also with Western philosophy. In these reflections on art, Sallis poses a critique of mimesis and considers the relation of painting to music. He affirms his conviction that the artist must always turn to nature, especially as reflections on the earth and sky delimit the scale and place of what is human. Full-color illustrations enhance this provocative and penetrating text."
Keywords: Cao, Jun -- 1966-; Philosophie; Malerei; Philosophy, American / 20th century; Influence (Literary, artistic, etc.); Philosophy, American; 1900-1999; Criticism, interpretation, etc